(untitled) (Clinics, 2014)
OBJECTIVE: The growth plate consists of organized hyaline cartilage and serves as a scaffold for endochondral ossification, a process that mediates longitudinal bone growth. Based on evidence showing that the oral administration of glucosamine sulfate (GS) and/or chondroitin sulfate (CS) is clinically valuable for the treatment of compromised articular cartilage, the current study evaluated the effects of these molecules on the tibial epiphyseal growth plate in female rats. METHOD: The animals were divided into two control groups, including vehicle treatment for 45 days (GC45) and 60 days (GC60) and six ovariectomized (OVX) groups, including vehicle treatment for 45 days (GV45), GS for 45 days (GE45GS), GS+CS for 45 days (GE45GS+CS), vehicle for 60 days (GV60), GS for 60 days (GE60GS) and GS+CS for 60 days (GE60GS+CS). At the end of treatment, the tibias were dissected, decalcified and processed for paraffin embedding. Morphological and morphometric methods were employed for analyzing the distal tibial growth plates using picrosirius red staining and the samples were processed for histochemical hyaluronan detection. Morphometric analyses were performed using the 6.0ProPlus¯ Image system. RESULTS: Notably, after 60 days of treatment, the number of proliferative chondrocytes increased two-fold, the percentage of remaining cartilage increased four-fold and the percentage of trabecular bone increased three-fold in comparison to the control animals. CONCLUSION: GS and CS treatment drugs led to marked cellular proliferation of the growth plate and bone formation, showing that drug targeting of the tibial epiphyseal growth plate promoted longitudinal bone growth.